Improving enzymatic hydrolysis efficiency of wheat straw through sequential autohydrolysis and alkaline post-extraction. (March 2018) - Wu, Xinxing; Huang, Chen; Zhai, Shengcheng; Liang, Chen; Huang, Caoxing; Lai, Chenhuan; Yong, Qiang
Highlights: A maximum enzymatic hydrolysis efficiency 83.7% was gained by two-step pretreatment. 65.6% Reduction of lignin with 2665.5 mg/g accessibilities was achieved. Relationships between enzymatic efficiency and substrate properties were summarized. Abstract: In this work, a two-step pretreatment process of wheat straw was established by combining autohydrolysis pretreatment and alkaline post-extraction. The results showed that employing alkaline post-extraction to autohydrolyzed wheat straw could significantly improve its enzymatic hydrolysis efficiency from 36.0% to 83.7%. Alkaline post-extraction lead to the changes of the structure characteristics of autohydrolyzed wheat straw. Associations between enzymatic hydrolysis efficiency and structure characteristics were also studied. The results showed that the factors of structure characteristics such as delignification, xylan removal yield, crystallinity, accessibility and hydrophobicity are positively related to enzymatic hydrolysis efficiency within a certain range for alkaline post-extracted wheat straw. The results demonstrated that autohydrolysis coupled with alkaline post-extraction is an effective and promising method to gain fermentable sugars from biomass.